2015
DOI: 10.5966/sctm.2014-0280
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Human Bone Marrow-Derived Mesenchymal Stromal Cell Extracellular Vesicles Ameliorates Aspergillus Hyphal Extract-Induced Allergic Airway Inflammation in Immunocompetent Mice

Abstract: There is a growing experience demonstrating benefit of mesenchymal stromal cell (MSC)-based cell therapies in preclinical models of asthma. In the current study, conditioned media (CM) and, in particular, the extracellular vesicle fraction obtained from the CM were as potent as the MSCs themselves in mitigating Th2/Th17-mediated allergic airway inflammation in a mouse model of severe refractory clinical asthma. Moreover, human MSC CM and extracellular vesicles were effective in this immunocompetent mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
191
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(194 citation statements)
references
References 53 publications
3
191
0
Order By: Relevance
“…Potentially related to their immune suppressive effects, MSC-derived EVs (MSC-EVs) exert beneficial therapeutic effects in animal models for different diseases, including acute kidney failure, myocardial infarction, ischemic stroke and asthma [1621]. Furthermore, MSC-EVs have been successfully used to treat a steroid-resistant Graft- versus -host disease (GvHD) patient without inducing any side effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Potentially related to their immune suppressive effects, MSC-derived EVs (MSC-EVs) exert beneficial therapeutic effects in animal models for different diseases, including acute kidney failure, myocardial infarction, ischemic stroke and asthma [1621]. Furthermore, MSC-EVs have been successfully used to treat a steroid-resistant Graft- versus -host disease (GvHD) patient without inducing any side effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Normal, adult human lung fibroblasts (HLF) (catalog number CCL-199; ATCC, Manassas, VA, http://www.atcc.org) were expanded in culture with Dulbecco’s Modified Eagle Medium: Nutrient Mixture F-12 (Sigma-Aldrich, St. Louis, MO, https://www.sigmaaldrich.com), 10% FBS, 1% Pen/Strep, and 2 mM l -glutamine and used at passage 6 or lower. We have previously demonstrated that HLFs can be successfully used as a control cell population in immunocompetent mouse models of allergic airway inflammation [16, 19, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…The ameliorating effects occur when the MSCs are administered either during initial antigen sensitization or at the onset of or during antigen challenge [920]. Some data also suggest that MSC administration can also protect against chronic or delayed antigen challenges [9, 18].…”
Section: Introductionmentioning
confidence: 99%
“…A dose-dependent inhibitory effect of MSC-derived extracellular vesicles on B-cell proliferation, differentiation and Ig production has been reported [58]. In a mouse model of severe refractory asthma, MSC-derived extracellular vesicles were as potent as the MSCs themselves in mitigating allergic airway inflammation [79]. In a model of hypoxia-induced pulmonary hypertension, treatment with MSC-derived exosomes ameliorated pulmonary hypertension and suppressed inflammation and alternative macrophage activation [80].…”
Section: Anti-inflammatory (M2) Mscs Inhibit the Cell Cycle Of Cytotmentioning
confidence: 98%